Multiple Inflammatory Prognostic Factors in Acute Coronary Syndromes: A Prospective Inception Cohort Study - Zinat Nadia Hatmi; Ali Kazemi Saeid; Mohammad Ali Broumand; Shabnam Najar Khoshkar; Zahra Fakher Danesh (Acta Medica Iranica, 2010)
Inflammatory basis in pathopoiesis of coronary artery disease (CAD) have been demonstrated in recent decades. Elevated C-Reactive Protein (CRP) and leukocytosis were associated with an elevated risk  for acute coronary syndrome (ACS). To evaluate the relationship between quantitative CRP and cardiac troponin I in conjunction with white blood cell (WBC) count and 30 days outcomes and treatment planning in patients with ACS. A concurrent inception cohort study was designed involving 200 patients as exposed and 200 patients as non exposed groups. We evaluated the relationship between baseline CRP and WBC count and cardiac troponin I , other risk factors and biomarkers, angiographic and other para-clinical tests and clinical outcomes with ACS. Higher CRP and WBC count were associated with additional coronary care unite (CCU) admission days (P = 0.002), hospitalization days (P = 0.007), arrhythmia type (P = 0.007), receiving streptokinase (P = 0.001), angiographic findings (P = 0.003), final myocardial infarction versus unstable angina (P = 0.001), date of complication (P = 0.001) and the date of cardiopulmonary resuscitation (if incident) (P = 0.015). In a multivariate Cox proportional hazard model high CRP and WBC count remained strong predictor of mortality (P = 0.028), angiography findings (three Vessel disease (3VD) and left main (LM) disease) (P = 0.001), and readmission in CCU (P = 0.002). A cardiac troponin I above 0.1 µg/lit was considered elevated. Elevated troponin level, demonstrated a significant relationship with MI incidence between two groups (P= 0.001) (89% in troponin positive group versus 11% in troponin less than 0.1 µg/lit). Inflammatory markers including, CRP and WBC count can be used to predict mortality, readmission, 3VD and LM disease in patients with ACS. In a Cox Proportional Hazard Model cardiac troponin above 0.1 µg/lit was significant predictors of MI (P = 0.003) and CPR (P = 0.044) at 30 days follow up period.